2002
DOI: 10.1002/ana.10254
|View full text |Cite
|
Sign up to set email alerts
|

Dyskinesias and grip control in Parkinson's disease are normalized by chronic stimulation of the subthalamic nucleus

Abstract: Deep-brain stimulation of the subthalamic nucleus appears to reduce levodopa-induced dyskinesias, but whether this effect is caused by the reduction of the total levodopa ingestion or represents a direct effect on the motor system is unknown. Precision grip force of grasping movements and levodopa-induced dyskinesias was analyzed in 10 parkinsonian patients before and after 3 months of deep-brain stimulation of the subthalamic nucleus. Peak grip force was abnormally increased before surgery in the off-drug sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 13 publications
1
21
1
2
Order By: Relevance
“…Importantly, the grip force excess was not related to the increased movement speed and must therefore be considered a direct result of STN stimulation. Our results seem to differ from those of Wenzelburger and colleagues, 30 who found normal grip force values in PD subjects tested after 3 months of STN stimulation, regardless of whether the stimulation was working or not and whether patients had taken levodopa or not. The difference may be due either to differences in patient selection or to the fact that these authors measured grip forces without relating them to inertial loads.…”
Section: Discussioncontrasting
confidence: 84%
“…Importantly, the grip force excess was not related to the increased movement speed and must therefore be considered a direct result of STN stimulation. Our results seem to differ from those of Wenzelburger and colleagues, 30 who found normal grip force values in PD subjects tested after 3 months of STN stimulation, regardless of whether the stimulation was working or not and whether patients had taken levodopa or not. The difference may be due either to differences in patient selection or to the fact that these authors measured grip forces without relating them to inertial loads.…”
Section: Discussioncontrasting
confidence: 84%
“…Dyskinesias were also dramatically reduced in severity and duration, most likely because dopaminergic medication was significantly reduced. However, chronic stimulation of the STN may have a direct effect on dyskinesias independent of the change in medication levels [14] . In our study, reduction in medication requirement was most pronounced in the first year.…”
Section: Discussionmentioning
confidence: 99%
“…These adaptation coefficients were based on linear regressions of the corresponding GF or MF force profile onto the LF profile (Scheidt et al, 2000;Joiner and Smith, 2008;Gonzalez Castro et al, 2011Joiner et al, 2011;Yousif and Diedrichsen, 2012;Wu et al, 2014;see Materials and Methods). We found that subjects exhibited significantly greater GF adaptation in the low-, medium-, and high-blocks compared with the zero-blocks ( p Ͻ 0.001 in all three cases, one-tailed paired t tests; Fig.…”
Section: Increased Environmental Variability Leads To Increases In Gfmentioning
confidence: 99%
“…This may explain why both healthy subjects under anesthesia (Westling and Johansson, 1984;Cole and Abbs, 1988;Nowak et al, 2001) and patients with a range of sensorimotor dysfunction exhibit elevated GF safety margins. In particular, elevated GFs have been reported in patients with multiple sclerosis (Iyengar et al, 2009), Parkinson's disease (Fellows et al, 1998;Wenzelburger et al, 2002), carpal tunnel syndrome (Zhang et al, 2011;Afifi et al, 2012), peripheral deafferentation , and cerebral stroke Dubrowski et al, 2005;Anens et al, 2010).…”
Section: Uncertainty-driven Control Of Gfs and Muscular Cocontractionmentioning
confidence: 99%